Recherche des effets in vitro d’un entomopathogène et des huiles essentielles de quatre plantes aromatiques (Lavandula sp., Origanum sp., Salvia sp. et Thymus sp.) sur les larves du ver blanc - ALLOUT, Nacer; SEKKOUTI, Ammi saïd (My University, 2020)
The white grub of crops causes considerable damage on several crops. It is considered a serious threat to agriculture in Algeria. Faced with this dangerous insect, farmers are oriented towards chemical control. The objective of this study is to propose alternative solutions based on the use of natural products in order to carry out biological control. The first part concerns the search for indigenous entomopathogens capable of controlling white grub populations. It focuses on the one hand on the isolation and identification of an entomopathogenic fungus present on a mummified larva of this insect and on the other hand, the demonstration of the larvicidal activity of this pathogen. The results obtained showed the existence of a single species of entomopathogenic fungus, namely: Fusarium sp .. The pathogenicity test of this strain confirms its causality in the induction of symptoms observed on the host. In addition, virulence tests on larvae highlight the effectiveness of this indigenous entomopathogen, with a mortality rate of over 60%. The second part of our work focuses on verifying the effectiveness of essential oils from four aromatic plants: Lavandula sp., Origanum sp., Salvia sp. and Thymus sp. on white grub larvae. The results obtained in vitro show that the larvae of the white grub are sensitive to the effect of EOs of Salvia sp. and Origanum sp. in comparison with that of the HEs of Lavandula sp. and Thymus sp .. The use of sage and oregano to control this pest has shown mortality rates of over 50% for Salvia sp. on the 10th day at a dose of 0.5% and on the 6th day at a dose of 1% for Origanum sp ..
Keywords: Bio-control; entomopathogenic fungus; essential oils; white grub